Influência do reboco e do reboco armado com tela soldada na resistência de alvenaria de vedação submetida à compressão simples - Lucilio Flavio Cyrino (2012)
Many buildings have been built using structural masonry techniques, with sealing bricks, which is not in accordance with the current technical standards. This has a direct impact in cost, but also in the building safety. In those constructions, there is no control of the tensile strength of the bricks, mortar and obviously, no structural analysis, which certantly implies the appearance of building pathologies. In order to recover such pathologies, or strength the masonry, it is suggested in the current work the use of cement render with a richer cement proportion or cement render with a welded mesh aplied in the wall built with the sealing brick. Thus, there is a net area gain of the application of the wall tension, resulting also in a greater inertia, which helps in the reduction and control of buckling. To do that, 9 walls were tested, and they were divided into uncoated walls (without revestiment), walls with cement render and walls with cement render and welded mesh . Of the tested walls, 3 had the following dimensions: 1.20m of length by 2.60m height , being 1 sample without cement render, 1with cement render only and 1 with cement render and welded mesh. The other 6 samples, with 0.90m of length by 1.04m height, were divided in pairs as the previous models: without cement render, with cement render only, and cement render and welded mesh. At the end of the axial compression tests, it was concluded that the application of the cement render ratio 1:6 (cement: sand), in volume, greatly increased the resistive capacity of the walls. The walls without cement render, had an increase up to 8 times in the tensile strength when compared with the others. Althought the tests carried out with the walls that had the welded mesh inserted in the cement render, were inconclusive, when they were compared with the uncoated walls, there was a significant increase in mechanical resistance. Thus it is concluded that the use of cement render in the masonry structure, which uses sealing bricks represents a significant increase in the tensile strength.